Effect of temperature on the rheological properties of neat aqueous Wyoming sodium bentonite dispersions - Vryzas, Zisis (2017)
Temperature affects significantly the rheological behavior of neat water Wyoming Na-bentonite dispersions. The results of a very systematic study are presented regarding rheological measurements of 7% mass concentration at different temperatures, ranging between 25 and 80 °C at atmospheric pressure. Higher temperature increased the shear stresses at low shear rates while the effect was much smaller at higher shear rates. The Herschel-Bulkley rheological model fitted extremely well all data. The yield stress increased linearly with temperature by almost three-fold, the flow consistency index decreased exponentially with temperature by almost five-fold and the flow behavior index increased by about 20%, tending towards the Newtonian value. At low shear rates (< 100 rpm corresponding to < 170 1/s Newtonian shear rates), which represent very well the shear rates experienced by drilling fluids in the critical annulus region, all rheograms appeared fairly linear and the Bingham plastic model fitted well all data. The Bingham yield stress, from the low shear rate data, increased linearly with temperature, while the plastic viscosity decreased with temperature, in a manner very similar to the decrease of water viscosity with temperature. The plastic viscosity and Bingham yield stress data, from the low shear rate range, can be fitted well by an Arrhenius-type equation, with the activation energy for the plastic viscosity very similar to the activation energy for water viscosity, while for the Bingham yield stress, the activation energy is equal but opposite in sign to that of the plastic viscosity. A hypothesis is stated for the the observed linear increase of the yield stress with temperature, in the temperature range studied. One should be concerned when non-standard preparation and measurement procedures are followed which makes extremely difficult to understand any differences observed when reporting rheological data of water bentonite dispersions. A standard methodology is proposed, complementary to API, which can give very consistent results.